RETRACTED: Lots of Chaotic Behaviors of the Henon Map - Alam, Md. Shakhawat; Ahmed, Payer (European Scientific Journal, ESJ, 2016)
This paper has been retracted on 27.11.2021. The reasons for the retraction are available in the retraction notice available on this website.